Molecular Dynamics Simulation of Bombardment of Hydrogen Atoms on Graphite Surface (Communications in Computational Physics, 2008)
The new potential model of interlayer intermolecular interaction was proposed to represent “ABAB” stacking of graphite. The bombardment of hydrogenatoms on the graphite surface was investigated using molecular dynamics simulation.Before the first graphene from the surface side was broken, the hydrogen atoms causedthe following processes. In the case of the incident energy of 5 eV, many hydrogenatoms were adsorbed on the front of the first graphite. In the case of the incident energy of 15 eV, almost all hydrogen atoms were reflected by the first graphene. In thecase of the incident energy of 30 eV, the hydrogen atoms were adsorbed between thefirst and second graphenes. The radial distribution function and the animation of theMD simulation demonstrated that the graphenes were peeled off one by one, which iscalled graphite peeling. One C2H2 was generated in such chemical sputtering. But theother yielded molecules often had chain structures terminated by the hydrogen atoms.The erosion yield increased linearly with time.